Effect of genotype and sex on breast meat quality characteristics of different chickens - Hailemariam, Atsbaha; Esatu, Wondmeneh; Abegaz, Solomon; Urge, Mengistu; Assefa, Getnet; Dessie, Tadelle (Elsevier, 2022)
This study examined the effects of different genotypes and sexes on the quality of breast meat in chickens. A total of 144 mixed-sex matured chicken genotypes of Cosmopolitan (C), Improved Horro (H), Cosmopolitan♂*Improved Horro♀(CH), Improved Horro♂*Cosmopolitan♀ (HC), Indigenous (L), and Koekoek (KK) were used. A completely randomized design in 6*2 factorial arrangements was deployed. All data were analyzed following the GLM model using SAS software (SAS, 2004). Lightness (L*), yellowness (b*), redness (a*), chroma (C*), and hue angle (h*) of the breast meat varied between sexes and genotypes. The breast's pH at 45 min and 24 h (pH45 and pH24) changed between the sexes and across genotypes. Water holding capacity (WHC) was highest for the L and H genotypes, then for HC, C, CH, and KK (P ≤ 0.001). The values of the breast shear force (WBSF) differed by genotype and by sex. The interactions between genotype and sex had an impact on the breast L*, b*, pH24, WHC, and WBSF values (P ≤ 0.05). Values for breast drip loss (DL) vary between sexes and genotypes. The cooking loss (CL) of KK, CH, and C chickens was considerably (P ≤ 0.01) higher than that of HC, H, and L chickens. The breast WBSF had an inverse and significant correlation with a* and WHC, but a positive significant correlation with DL, CL, L*, b*, C*, and h*. Breast meat quality was best in the L and H genotypes, then in the HC, C, CH, and KK genotypes. Genotype and sex variants had a greater impact on breast quality differences than did their interactions.